Contract farming and Indian agriculture: Can agribusiness help the small farmer? - Swain, Braja B. (2016)
Farming based on a contract between farmers and agro-processing and/or marketing firms is catching on in Indian agriculture due to increase the demand for processed products, change in consumption pattern, conducive policy environment. The logic behind the promotion of this form of farming is to encourage private investment in agriculture and to reduce price risks as well as post-harvest losses, especially risk oriented fruits, vegetables and high value crops. The private sector may play a role in providing a range of services to small holders from input supply to crop assembly and marketing. In this context, the present paper explores at what extent contract farming would remove the constraints faced by small holders in Indian agriculture and help them to move out from poverty trap. It was observed that contract farming cannot be seen as a panacea for all the problems afflicting the Indian agriculture while it has the potential to address the problems relating to access to market (input and output), new technology and price stability, it generates the problems like degradation of traditional knowledge, soil quality and bias towards large farmers. There needs for a better institutional mechanism to make contract farming more inclusive and sustainable.